Basis for Study of Compatibility, and of Compatibility of the Colon Classification with the Universal Decimal Classification - Ranganathan, S. R.; Neelameghan, A. (Journal of Information and Knowledge, 1989)
Five types of compatibility studies are possible between document-finding systems. A Basis of Reference for compatibility studies is given, in terms of the dominant purpose and of the factors in the mental set of the majority of the readers seeking the service of the system. A document-finding system should have an efficient scheme for classification built into it. The latter should be based on a sound and dynamic theory of classification. The essential features of the current general theory of classification are indicated. The extent to which CC and UDC conform to it is examined. Illustrates, with examples, the compatibility of CC-in-Theory with UDC-in-Theory and of CC-in-Action with UDC in- Action. Even though UDC-in-Theory may not be fully compatible with CC-in-Theory, UDC-in-Action can be made compatible with CC-in-Action and with the Basis of Reference with the aid of the guiding principles given in the Guide to U DC (1963). These principles are in conformity with the general theory of classification. The advantages of basing an electronic document-finding system on an efficient scheme for classification and the compatibility of CC and UDC for the purpose are mentioned. The additional advantage of using CC is indicated.